PEMBELAJARAN KJU!:ATIF-KJUTIS BERMUATAN HARD-SKILL DAN SOFT-SKILL MATA KULIAH ILMU PENDIDIKAN - Yoyon Suryono (MAJALAH ILMIAH PEMBELAJARAN, 2007)
The purpose of the teaching through critical-creative learningmodel grant for educational science subject is to improve student 'sawareness of hard skill and .~·oft skill as two significant elemrnts ofcompetencies that non formal education students must have. Tl.egrant results, which is a learning model to gain hard skill and softskill a11d a critical-creative learning model, is appiicable for othersubjects and even other study programs. Critical-creative learningmodel is able to develop student 's mastery in hard skill and softskill. The implementation of critical-creative learning model can beref er to woup di.\cu:;sion approach, concept understandir.gassignments, and problem solving assignments either individually orin groups. Howevu, further elaboration of hard skill and soft skillcompetency and critical-creative learning model must always bedone through other subject using different model, strategy, method·and approach.